ActionAid International Kenya’s Initiatives in Fostering Good Governance in Garissa County, Kenya - Dahir, Mohamed; Moi, Edna (Journal of Public Policy and Administration, 2025)
Purpose: The study sought to assess the effectiveness of ActionAid International Kenya’s initiatives in fostering good governance in Garissa County. Specifically, it examined the influence of grassroots advocacy, legal support, and community mobilization on governance outcomes. Methodology: A descriptive cross-sectional design was used to evaluate how selected governance strategies affect local public participation and transparency. The sample comprised 177 respondents selected through stratified random sampling. Data was collected using structured questionnaires and analyzed through descriptive statistics and Pearson product-moment correlation using SPSS version 26. Findings: Results revealed that grassroots advocacy had a mean of 3.40 (r = 0.507, p < 0.001), legal support had a mean of 3.26 (r = 0.548, p < 0.001), and community mobilization had a mean of 3.33 (r = 0.614, p < 0.001), indicating strong positive relationships with good governance outcomes. Unique Contribution to Theory, Practice and Policy: The study supports Participatory Governance Theory and Accountability Theory by emphasizing the importance of civic involvement and institutional transparency. Practically, it recommends strengthening grassroots forums, legal aid accessibility, and community mobilization efforts.